EFEITO DA SALINIDADE NA GERMINAÇÃO E DESENVOLVIMENTO INICIAL DA LEUCENA - Nóbrega, Gorgônio Maurício Da; Queiroz, José Elenildo; Silva, Lígia Maria De Medeiros [UNESP]; Santos, Rivaldo Vital Dos (Departamento de Engenharia Agrícola - UFCG, 1999)
This work was carried out with the objective of evaluating the effect of different levels of NaCl in the germination and initial development of the leucena (Leucaena leucocephala (Lam) of Wit.). The experiment was conducted in a greenhouse, using NaCl for artificial salinization of the soil, to obtain e concentrations of 0.15; 0.30; 0.45 and 0.60% (ECseof 6, 12, 18 and 24 dS m-1). The following variables were analyzed: germination percentage, index of germination velocity, leaf area, height of plants and dry matter. The analysis of the data demonstrated that the potential of germination of the leucena was affected with the increase of the concentration of NaCl. The initial development of the leucena suffered a more significative effect at 0.45%, but the variables leaf area and dry matter were affected starting from the concentrations of 0.15 and 0.30%, respectively.

Este trabalho teve por objetivo avaliar o efeito de diferentes níveis de NaCl na germinação e desenvolvimento inicial da leucena (Leucaena leucocephala (Lam.) de Wit.). O experimento foi conduzido em casa-de-vegetação, tendo-se utilizado NaCl para salinização artificial do solo, de modo a se obter as concentrações de 0,15; 0,30; 0,45 e 0,60% (CEesiguais a 6, 12, 18 e 24 dS m-1). Analisaram-se as seguintes variáveis: percentagem de germinação, índice de velocidade de germinação (IVG), área foliar, altura de plantas e matéria seca. A análise dos dados demonstrou que o potencial de germinação da leucena foi afetado com o aumento da concentração de NaCl e que o desenvolvimento inicial da leucena sofreu efeito mais significativo a partir da concentração de 0,45%, mas as variáveis área foliar e matéria seca foram afetadas a partir de 0,15 e 0,30%, respectivamente.
EFFECT OF SALINITY IN GERMINATION AND INITIAL DEVELOPMENT OF THE LEUCENA
Keywords: Leucena leucocephala; salinity tolerance; germination; Leucaena leucocephala; tolerância a salinidade; germinação